Nutrition and Avoidance Diets in Children With Food Allergy - Corica, Domenico; Aversa, Tommaso; Caminiti, Lucia; Lombardo, Fortunato; Wasniewska, Malgorzata; Pajno, Giovanni Battista (Frontiers in Pediatrics, 2020)
Food allergy (FA) is a significant health issue which considerably influences the quality of life of both children and their family. The increasing prevalence of FA, documented in the last 3 decades, has led to the reassessment of FA prevention strategies and particularly to giving up the approach based on delaying the introduction of potential food allergens. Several observational and interventional studies demonstrated a potential effectiveness of the early food introduction strategy in FA prevention, although strong evidence from randomized controlled trials are lacking and, sometimes, contrasting. The current approach to FA is mainly based on avoidance diet and the use of rescue medications in case of allergic reaction, although active allergen immunotherapy has recently become an increasingly important therapeutic strategy to approach IgE-mediated FA, potentially able to induce improvement through desensitization to a specific food. This review provides an overview on the historical evolution of recommendations about FA and on evidence published in the last 15 years on nutritional intervention strategy, i.e., early introduction of allergen or avoidance diet, in the prevention and management of IgE-mediated and non-IgE-mediated FA in children.